Persepsi Masyarakat terhadap Alun-alun Kalirejo sebagai Ruang Publik Kota Ungaran - Dyah Candrarini; Hadi Wahyono (Jurusan Perencanaan Wilayah dan Kota, 2018)
Urban areas are regions with non-agricultural activities. The composition of urban areas functions as settlement, centralization and distribution of government services, social services, and economic activities. One of the urban social service facilities is public space. Square is one form of the public space that the service covers entire city. In Indonesia, the existence of the square is believed to serve as a center of public activity that eventually leads as an icon of a city. In 2014, the Government of Ungaran City inaugurated a square namely Kalirejo Square. Ungaran City has previously had two square that so cramped to do activities in it. So it does not take long, Kalirejo Square instantly has its own charm, considering this is a new thing for the citizens of Ungaran City. Its strategic location, which is straight on the exit of Ungaran Highway, create wide range of services area. Ocasionally encountered visitors from outside the city of Ungaran. The spacious field is also able to provide various facilities to meet the needs of visitors, such as playgrounds, street vendors, parking lots, meeting hall, green fields, toilets, prayer room (musala), up to the arena of tour vehicles and skates. Based on this background, the research question arises that is